2015
DOI: 10.1002/jwmg.913
|View full text |Cite
|
Sign up to set email alerts
|

Demography, prey abundance, and management affect number of cougar mortalities associated with livestock conflicts

Abstract: Balancing the ecological importance of large carnivores with human tolerances across multiple‐use landscapes presents a complex and often controversial management scenario. Increasing cougar (Puma concolor) populations in the western United States, coupled with an increasing human population and distribution, may contribute to increased numbers of interactions and conflicts (e.g., livestock depredation) with cougars. We assessed county‐level factors associated with mortalities of cougars of different sexes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Because reduced availability of natural prey may increase large feline depredation [ 74 , 75 ] and wild prey may serve to buffer livestock from puma predation [ 76 , 77 ], land management that facilitates a greater abundance of wild prey may also potentially decrease depredation by pumas in the rangelands of central Argentina.…”
Section: Discussionmentioning
confidence: 99%
“…Because reduced availability of natural prey may increase large feline depredation [ 74 , 75 ] and wild prey may serve to buffer livestock from puma predation [ 76 , 77 ], land management that facilitates a greater abundance of wild prey may also potentially decrease depredation by pumas in the rangelands of central Argentina.…”
Section: Discussionmentioning
confidence: 99%
“…Third, several recent studies on managing wildlife have suggested that animals should be removed based on their demographic class [9,26,40,52,53]. In Australia, removing large male cats Felis catus is considered a conservation priority owing to their ability to take large native prey [26] while, in the Baltic Sea, adult male grey seals Halichoerus grypus are significantly more likely to be responsible for damage to fishing gear [52].…”
Section: Evaluating Managementmentioning
confidence: 99%
“…In Kenya, male elephants were responsible for 86% of fencebreaking incidents [22]. In an attempt to refine lethal management, several recent studies have explicitly directed wildlife managers towards removing male animals [40,52,53]. The deliberate or unintentional targeting of males can, however, have detrimental effects; male removal and the skewing of natural sex ratios can alter community structure and sexual selection processes, produce an increase in infanticide and female harassment, and potentially remove the benefits of biparental care [66,67].…”
Section: Box 4 Case Study -'Bruno the Bear' And The Power Of The Individualmentioning
confidence: 99%
“…Habitat loss and poaching are primary threats to wild felids (Zeller 2007;IUCN 2008;Loveridge et al 2010). People kill jaguars (Panthera onca) and pumas (Puma concolor) for their skin and bones, for recreation, because of chance encounters, as a retaliatory response for livestock depredation, and because of the perceived threat to themselves and livestock (Carvalho and Pezzuti 2010;Loveridge et al 2010;Robinson et al 2014;Hiller et al 2015). Commercial hunting for pelts has historically driven the decline of jaguars in Central and South America.…”
Section: Introductionmentioning
confidence: 99%